Time-periodic Solutions to Systems of Conservation Laws with Ellipticity (Journal of Partial Differential Equations, 1999)
We study the time-periodic solutions to systems of conservation laws with ellipticity. It is shown that under time-periodic boundary condition, the system admits at least one global time-periodic solution bounded uniformly with the same period.
Keywords: Time-periodic solutions; ellipticity